CUSTOMIZED BIOMODEL OF THE CERVICAL SPINE FOR LABORATORY LAMINOPLASTY TRAINING - Araújo-Júnior , Francisco Alves de (2024)
Background: Additive manufacturing has been developed as a promising innovation for many areas, including medicine. There are many ways to use it in spine surgeries and the use of biomodels in the laboratory to study and training of cervical laminoplasty has not yet been reported in the literature. Objective: To evaluate the use of a biomodel of the cervical spine for surgical training of laminoplasty. Method: This is an experimental study. Were printed 10 identical biomodels of the cervical spine based on CT and MRI scans of a patient diagnosed with spondylotic cervical myelopathy. The additive manufacturing method used was fused deposition modeling and the raw material chosen was polyatic acid. The sample was divided into 2 groups: control (n = 5; the biomodels were submitted to CT scanning) and open-door (n = 5; the biomodels were submitted to open-door laminoplasty and postoperative CT). The area and anteroposterior diameter of the vertebral canal were measured on CT scans. Result: The time for printing each piece was 12 h. During the surgical procedure, the support of the biomodels was sufficient to keep them static. The use of drill was feasible; however, continuous irrigation was mandatory to prevents the heating of the plastic material. The raw material used allowed the CT study of the biomodels. It was observed an increase the dimensions of the vertebral canal in 24,80% (0.62 cm2) in the area and 24,88% (3.12 mm) in the anteroposterior diameter. Conclusion: The cervical spine biomodels can be used for laminoplasty training, even using thermosensitive material such as PLA. The use of continuous irrigation is essential during the use of the drill.